(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Of the subject relevance. of Uzbekistan economic and social development chemistry industry products work release continuous increase, new polymer materials and of them prepared items appropriation and a person of activity all polymer carpet products Current at the time polymer carpet products (PGM) daily in life, administrative and public in buildings, car showrooms cover material as wide is used.